Assessment of soil degradation in northern Basrah governorate using geospatial techniques and spectral Indices - Hassan Mohamed Raml; Mohammed A. Kadhim (University of Thi-Qar Journal of agricultural research, 2024)
This study was conducted to evaluate the degradation of soils in northern Basra Governorate using remote sensing techniques, geographic information systems and some spectral indicators. The soils of the region are characterized by being of calcareous sedimentary origin, belonging to the Entisols rank. The study area is located north of Basra Governorate, southern Iraq, within the administrative borders of Al-Qurna District, extending south to Al-Deir District. It is bordered to the east by the Shatt Al-Arab River and lies between longitudes 47°22’10" - 47°39’8" east and latitudes 30°44’41" - 31°3’49" north, with an area of ​​429.681 km2. The results of the physical analysis showed that there was a difference in the distribution pattern of soil particles (sand, silt and clay) within a single soil site or between different soil sites. This is due to the variation in the sedimentary environment of the studied sites. It was noted that the content of clay and silt was high in general depths of the sites compared to the small amount of sand in some sites. The dominance of silt particles was in most sites, ranging between 206.90 - 703.20 g kg-1, then clay, ranging between 202.80 - 659.20 g kg-1, while sand ranged between 16.40 - 425.30 g kg-1. The results of the chemical analysis showed that the organic matter content of the sites ranged between 2.1 - 16.6 g kg-1. The highest values ​​appeared in the surface depths, especially at site 6, and the soil salinity ranged between non-saline soils and highly saline soils, ranging from 3.33 to 90.82 dsm-1. The lowest salinity appeared at site 4, reaching 3.33 dsm-1, which is affiliated with the Kutuf Al-Anhar section located east of Shatt Al-Arab.